PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR INDUSTRI METAL, PAKAN TERNAK, KERTAS, DAN KAYU YANG TERDAFTAR DI BEI 2009-2013 - Olgawati Hudoyo (Business Accounting Review, 2015)
The objective of this research was to identify the influence of Corporate Social Responsibility, which was  measured based on Global Reporting Initiative 3.1 on firm value, which was measured by Tobin’s Q. The sample is taken from 105 observations in metal industry, animal feed, pulp and paper, and wood companies  listed in BEI in 2009-2013. The result showed  that CSR significant influence on firm value. Whereas, the control variables of firm value and debt to equity ratio had no significant influence on firm value. While market share, had significant influence on firm value.